Strategies for Religious Teachers in Increasing Reading Interest and Memorizing Juz 30 - Ian Inayah Sari; Fitri Umardiyah; Khusnul Khotimah; M. Farid Nasrulloh (SCHOOLAR: Social and Literature Study in Education, 2024)
This study aims to: 1) find out the strategies of religious teachers in increasing interest in reading and memorizing the Alquran juz 30 in students at SDN Kabuh, 2) find out the supporting and inhibiting factors of the strategies of religious teachers in increasing interest in reading and memorizing the Alquran juz 30 in students at Kabuh Elementary School. To achieve the above objectives, a qualitative approach is used with this type of research is field research. Research informants are school principals, religious teachers and students. The results of this study indicate that, 1) The strategy of religious teachers in increasing interest in reading and memorizing the Alquran juz 30 for students at SDN Kabuh is to create comfortable learning when reading and writing the Alquran takes place, providing motivation to children in the form of explanations and understanding of the importance of memorizing and reading Alquran juz 30 for them especially for their life in the world and in the hereafter, providing memorization targets, through habituation, giving grades, and finally giving awards, 2) Supporting factors for religious teachers in increasing interest in reading and memorizing the Alquran juz 30 for students namely, participants the students themselves, the role of a teacher, adequate facilities, there are also inhibiting factors, namely the lack of time allocation, lack of parental awareness, then the negative influence of technology.